Chinese censorship of online discourse - Juha Vuori; Lauri Paltemaa (Routledge, 2022)
In this chapter we explore how practices of security governmentality are enacted in everyday
censorship of online discourse in China. We do this by showing how internet censorship can be
approached as a form of controlling the fl ow of ‘good’, ‘bad’, and ‘dangerous’ words and images.
Together with propaganda, censorship, even on the level of words, is part of how political discourse
is controlled in China. We illustrate this with two case studies that display what we call
overt and covert meta-level censorship on China’s largest microblog service Sina Weibo and her
largest search engine Baidu.com respectively.
Our analysis shows how meta-level search engine fi ltering is based on a two-layered system,
where short-lived political incidents tend to be fi ltered for brief periods of time, while words
that are conducive to building oppositional awareness tend to be censored more continuously.
Controlling discourse in this way affects identity formation and power positions ( Fairclough,
1992 ) in Chinese society. Furthermore, censorship is used to sanitize images in the Chinese
internet in order to create a neutral or pro-regime online environment for Chinese internet
users, in our case, where it concerns the issue of democratic criticism. We begin the chapter by
fi rst introducing our framework and the main tenets of research on Chinese internet control.
We then present our two case studies on internet control over social media and search engines
on Sina Weibo and Baidu.
The Routledge Handbook of Chinese Discourse Analysis